2014
DOI: 10.1007/s11136-014-0656-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological pathways, candidate genes, and molecular markers associated with quality-of-life domains: an update

Abstract: Background There is compelling evidence of a genetic foundation of patient-reported QOL. Given the rapid development of substantial scientific advances in this area of research, the current paper updates and extends reviews published in 2010. Objectives The objective is to provide an updated overview of the biological pathways, candidate genes and molecular markers involved in fatigue, pain, negative (depressed mood) and positive (well-being/happiness) emotional functioning, social functioning, and overall Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 65 publications
1
65
0
Order By: Relevance
“…In contrast, individuals with two doses of the rare G allele for nuclear factor kappa beta 2 ( NFKB2 ) rs12772374 had a 47.7 fold increase in the odds of belonging to the lower QOL class. These findings add to the growing body of evidence that QOL has a genetic basis [44]. …”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In contrast, individuals with two doses of the rare G allele for nuclear factor kappa beta 2 ( NFKB2 ) rs12772374 had a 47.7 fold increase in the odds of belonging to the lower QOL class. These findings add to the growing body of evidence that QOL has a genetic basis [44]. …”
Section: Introductionmentioning
confidence: 53%
“…Nonetheless, this study adds to the growing body of evidence of genomic involvement in QOL outcomes [44]. The genetic association identified suggests a relationship between a cytokine gene polymorphism and decrements in social well-being.…”
Section: Discussionmentioning
confidence: 77%
“…Studies of genomic encoding for fatigue are now beginning to explore the increased activity of proinflammatory transcription factors as contributors to fatigue [22,23]. A study of breast cancer survivors with persistent fatigue found increased expression of inflammation-related genes, particularly those responsive to the proinflammatory nuclear factor-κB transcription control pathway, together with a decreased expression of glucocorticoid-dependent anti-inflammatory genes [24].…”
Section: What Causes Crf?mentioning
confidence: 99%
“…Other researchers have reported other biological pathways, candidate genes, and genetic markers for CRF, such as genes related to dopaminergic synapse (COMT, DRD4, and DAT1; Rausch et al, 2010) and cytokine-cytokine receptor interaction (interleukin [IL]-1b, IL-1 receptor antagonist (IL-1RA), IL-6, and tumor necrosis factor [TNF]-a; Aouizerat et al, 2009;Saligan & Kim, 2012;Thornton, Andersen, & Blakely, 2010). However, there are very limited association studies that propose genetic markers for CRF using a wholegenome approach (Sprangers et al, 2014). In the present study, we use whole-genome microarray to explore the association of changes in fatigue with changes in gene expression from RNA of peripheral blood mononuclear cells from fatigued men receiving EBRT for nonmetastatic prostate cancer.…”
mentioning
confidence: 99%